Position-dependent impact of hexafluoroleucine and trifluoroisoleucine on protease digestion - Huhmann, Susanne; Stegemann, Anne-Katrin; Folmert, Kristin; Klemczak, Damian; Moschner, Johann; Kube, Michelle; Koksch, Beate (Beilstein Journal of Organic Chemistry, 2017)
Rapid digestion by proteases limits the application of peptides as therapeutics. One strategy to increase the proteolytic stability of peptides is the modification with fluorinated amino acids. This study presents a systematic investigation of the effects of fluorinated leucine and isoleucine derivatives on the proteolytic stability of a peptide that was designed to comprise substrate specificities of different proteases. Therefore, leucine, isoleucine, and their side-chain fluorinated variants were site-specifically incorporated at different positions of this peptide resulting in a library of 13 distinct peptides. The stability of these peptides towards proteolysis by α-chymotrypsin, pepsin, proteinase K, and elastase was studied, and this process was followed by an FL-RP-HPLC assay in combination with mass spectrometry. In a few cases, we observed an exceptional increase in proteolytic stability upon introduction of the fluorine substituents. The opposite phenomenon was observed in other cases, and this may be explained by specific interactions of fluorinated residues with the respective enzyme binding sites. Noteworthy is that 5,5,5-trifluoroisoleucine is able to significantly protect peptides from proteolysis by all enzymes included in this study when positioned N-terminal to the cleavage site. These results provide valuable information for the application of fluorinated amino acids in the design of proteolytically stable peptide-based pharmaceuticals.
Keywords: fluorinated amino acids; hexafluoroleucine; peptide drugs; protease stability; trifluoroisoleucine

(untitled) - Vlieghe, P.; Lisowski, V.; Martinez, J.; Khrestchatisky, M. (Drug Discovery Today, 2010)

(untitled) - Sato, A. K.; Viswanathan, M.; Kent, R. B.; Wood, C. R. (Curr. Opin. Biotechnol., 2006)

(untitled) - Albericio, F.; Kruger, H. G. (Future Med. Chem., 2012)

(untitled) - Uhlig, T.; Kyprianou, T.; Martinelli, F. G.; Oppici, C. A.; Heiligers, D.; Hills, D.; Calvo, X. R.; Verhaert, P. (EuPa Open Proteomics, 2014)

(untitled) - Fosgerau, K.; Hoffmann, T. (Drug Discovery Today, 2015)

(untitled) - Santos, G. B.; Ganesan, A.; Emery, F. S. (ChemMedChem, 2016)

(untitled) - Jäckel, C.; Koksch, B. (Eur. J. Org. Chem., 2005)

(untitled) - Latham, P. W. (Nat. Biotechnol., 1999)

(untitled) - Salwiczek, M.; Nyakatura, E. K.; Gerling, U. I. M.; Ye, S.; Koksch, B. (Chem. Soc. Rev., 2012)

(untitled) - Berger, A. A.; Völler, J.-S.; Budisa, N.; Koksch, B. (Acc. Chem. Res., 2017)

(untitled) - Salwiczek, M.; Samsonov, S.; Vagt, T.; Nyakatura, E.; Fleige, E.; Numata, J.; Cölfen, H.; Pisabarro, M. T.; Koksch, B. (Chem. – Eur. J., 2009)

(untitled) - Huhmann, S.; Nyakatura, E. K.; Erdbrink, H.; Gerling, U. I. M.; Czekelius, C.; Koksch, B. (J. Fluorine Chem., 2015)

Methods in Enzymology - Marsh, E. N. G. (Designing Fluorinated Proteins, 2016)

Modern Synthesis Processes and Reactivity of Fluorinated Compounds - Vukelić, S.; Moschner, J.; Huhmann, S.; Fernandes, R.; Berger, A. A.; Koksch, B. (Synthesis of Side Chain Fluorinated Amino Acids and Their Effects on the Properties of Peptides and Proteins, 2017)

(untitled) - Buer, B. C.; Meagher, J. L.; Stuckey, J. A.; Marsh, E. N. G. (Protein Sci., 2012)

(untitled) - Buer, B. C.; Meagher, J. L.; Stuckey, J. A.; Marsh, E. N. G. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Jäckel, C.; Salwiczek, M.; Koksch, B. (Angew. Chem., Int. Ed., 2006)

(untitled) - Tang, Y.; Tirrell, D. A. (J. Am. Chem. Soc., 2001)

(untitled) - Tang, Y.; Ghirlanda, G.; Petka, W. A.; Nakajima, T.; DeGrado, W. F.; Tirrell, D. A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Tang, Y.; Ghirlanda, G.; Vaidehi, N.; Kua, J.; Mainz, D. T.; Goddard, W. A., III; DeGrado, W. F.; Tirrell, D. A. (Biochemistry, 2001)

(untitled) - Yoder, N. C.; Kumar, K. (Chem. Soc. Rev., 2002)

(untitled) - Bilgiçer, B.; Xing, X.; Kumar, K. (J. Am. Chem. Soc., 2001)

(untitled) - Meng, H.; Kumar, K. (J. Am. Chem. Soc., 2007)

(untitled) - Deacon, C. F.; Nauck, M. A.; Toft-Nielsen, M.; Pridal, L.; Willms, B.; Holst, J. J. (Diabetes, 1995)

(untitled) - Holst, J. J.; Deacon, C. F. (Curr. Opin. Pharmacol., 2004)

(untitled) - Drucker, D. J. (Curr. Pharm. Des., 2001)

(untitled) - Meng, H.; Krishnaji, S. T.; Beinborn, M.; Kumar, K. (J. Med. Chem., 2008)

(untitled) - Akçay, G.; Kumar, K. (J. Fluorine Chem., 2009)

(untitled) - Gottler, L. M.; Lee, H.-Y.; Shelburne, C. E.; Ramamoorthy, A.; Marsh, E. N. G. (ChemBioChem, 2008)

(untitled) - Voloshchuk, N.; Zhu, A. Y.; Snydacker, D.; Montclare, J. K. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Budisa, N.; Wenger, W.; Wiltschi, B. (Mol. BioSyst., 2010)

(untitled) - Bordusa, F.; Dahl, C.; Jakubke, H.-D.; Burger, K.; Koksch, B. (Tetrahedron: Asymmetry, 1999)

(untitled) - Koksch, B.; Sewald, N.; Burger, K.; Jakubke, H.-D. (Amino Acids, 1996)

(untitled) - Koksch, B.; Sewald, N.; Hofmann, H.-J.; Burger, K.; Jakubke, H.-D. (J. Pept. Sci., 1997)

(untitled) - Smits, R.; Koksch, B. (Curr. Top. Med. Chem., 2006)

(untitled) - Thust, S.; Koksch, B. (J. Org. Chem., 2003)

(untitled) - Thust, S.; Koksch, B. (Tetrahedron Lett., 2004)

(untitled) - Sewald, N.; Hollweck, W.; Mütze, K.; Schierlinger, C.; Seymour, L. C.; Gaa, K.; Burger, K.; Koksch, B.; Jakubke, H. D. (Amino Acids, 1995)

(untitled) - Asante, V.; Mortier, J.; Schlüter, H.; Koksch, B. (Bioorg. Med. Chem., 2013)

(untitled) - Asante, V.; Mortier, J.; Wolber, G.; Koksch, B. (Amino Acids, 2014)

(untitled) - Schechter, I.; Berger, A. (Biochem. Biophys. Res. Commun., 1967)

(untitled) - Davies, D. R. (Annu. Rev. Biophys. Biophys. Chem., 1990)

(untitled) - Zhao, Y. H.; Abraham, M. H.; Zissimos, A. M. (J. Org. Chem., 2003)

(untitled) - Erdbrink, H.; Nyakatura, E. K.; Huhmann, S.; Gerling, U. I. M.; Lentz, D.; Koksch, B.; Czekelius, C. (Beilstein J. Org. Chem., 2013)

(untitled) - Samsonov, S. A.; Salwiczek, M.; Anders, G.; Koksch, B.; Pisabarro, M. T. (J. Phys. Chem. B, 2009)

(untitled) - Blow, D. M.; Birktoft, J. J.; Hartley, B. S. (Nature, 1969)

The Enzymes - Blow, D. M. (The Structure of Chymotrypsin, 1971)

(untitled) - Derewenda, Z. S.; Derewenda, U.; Kobos, P. M. (J. Mol. Biol., 1994)

(untitled) - Polgár, L. (Cell. Mol. Life Sci., 2005)

Advances in Enzymology and Related Areas of Molecular Biology - Fruton, J. S. (The Specificity and Mechanism of Pepsin Action, 1970)

The Enzymes - Fruton, J. S. (Pepsin, 1971)

(untitled) - Dunn, B. M. (Chem. Rev., 2002)

Acid Proteases:Structure, Function, and Biology - Antonov, V. K. (New Data on Pepsin Mechanism and Specificity, 1977)

Acid Proteases:Structure, Function, and Biology - Powers, J. C.; Harley, A. D.; Myers, D. V. (Subsite Specificity of Porcine Pepsin, 1977)

(untitled) - Largman, C.; Brodrick, J. W.; Geokas, M. C. (Biochemistry, 1976)

Methods in Enzymology - Shotton, D. M. (Elastase, 1970)

Enzymes of Molecular Biology - Sweeney, P. J.; Walker, J. M. (Proteinase K (EC 3.4.21.14), 1993)

(untitled) - Czapinska, H.; Otlewski, J. (Eur. J. Biochem., 1999)

(untitled) - Hedstrom, L. (Chem. Rev., 2002)

Enzymes of Molecular Biology - Sweeney, P. J.; Walker, J. M. (Proteolytic Enzymes for Peptide Production, 1993)

(untitled) - Brady, K.; Abeles, R. H. (Biochemistry, 1990)

(untitled) - Schellenberger, V.; Jakubke, H.-D. (Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1986)

(untitled) - Schellenberger, V.; Turck, C. W.; Rutter, W. J. (Biochemistry, 1994)

(untitled) - Ye, S.; Loll, B.; Berger, A. A.; Mülow, U.; Alings, C.; Wahl, M. C.; Koksch, B. (Chem. Sci., 2015)

(untitled) - Antal, J.; Pál, G.; Asbóth, B.; Buzás, Z.; Patthy, A.; Gráf, L. (Anal. Biochem., 2001)

(untitled) - Sampath-Kumar, P. S.; Fruton, J. S. (Proc. Natl. Acad. Sci. U. S. A., 1974)

(untitled) - Fruton, J. S. (Acc. Chem. Res., 1974)

(untitled) - Hamuro, Y.; Coales, S. J.; Molnar, K. S.; Tuske, S. J.; Morrow, J. A. (Rapid Commun. Mass Spectrom., 2008)

Aspartic Proteinases: Structure, Function, Biology, and Biomedical Implications - Rao, C.; Dunn, B. M. (Evidence for Electrostatic Interactions in the S2 Subsite of Porcine Pepsin, 1995)

(untitled) - Fujinaga, M.; Chernaia, M. M.; Mosimann, S. C.; James, M. N. G.; Tarasova, N. I. (Protein Sci., 1995)

(untitled) - Kageyama, T. (Cell. Mol. Life Sci., 2002)

(untitled) - Dunn, B. M.; Hung, S.-H. (Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 2000)

(untitled) - Naughton, M. A.; Sanger, F. (Biochem. J., 1961)

(untitled) - Renaud, A.; Lestienne, P.; Hughes, D. L.; Bieth, J. G.; Dimicoli, J. L. (J. Biol. Chem., 1983)

(untitled) - Qasim, M. A. (Protein Pept. Lett., 2014)

(untitled) - Atlas, D. (J. Mol. Biol., 1975)

(untitled) - Atlas, D.; Levit, S.; Schechter, I.; Berger, A. (FEBS Lett., 1970)

(untitled) - Ebeling, W.; Hennrich, N.; Klockow, M.; Metz, H.; Orth, H. D.; Lang, H. (Eur. J. Biochem., 1974)

(untitled) - Georgieva, D.; Genov, N.; Voelter, W.; Betzel, C. (Z. Naturforsch., C: J. Biosci., 2006)

(untitled) - Morihara, K.; Tsuzuki, H. (Agric. Biol. Chem., 1975)

(untitled) - Brömme, D.; Peters, K.; Fink, S.; Fittkau, S. (Arch. Biochem. Biophys., 1986)

(untitled) - Kraus, E.; Femfert, U. (Hoppe-Seyler's Z. Physiol. Chem., 1976)

(untitled) - Betzel, C.; Singh, T. P.; Visanji, M.; Peters, K.; Fittkau, S.; Saenger, W.; Wilson, K. S. (J. Biol. Chem., 1993)

(untitled) - Wolf, W. M.; Bajorath, J.; Müller, A.; Raghunathan, S.; Singh, T. P.; Hinrichs, W.; Saenger, W. (J. Biol. Chem., 1991)

(untitled) - Betzel, C.; Bellemann, M.; Pal, G. P.; Bajorath, J.; Saenger, W.; Wilson, K. S. (Proteins: Struct., Funct., Genet., 1988)

(untitled) - Kraus, E.; Kiltz, H.-H.; Femfert, U. F. (Hoppe-Seyler's Z. Physiol. Chem., 1976)